Comparison of the anti-colitis activities of Qing Dai/Indigo Naturalis constituents in mice - Kei Ozawa; Daichi Mori; Ayumu Hatanaka; Toshinori Sawano; Jin Nakatani; Yukinobu Ikeya; Mikio Nishizawa; Hidekazu Tanaka (Elsevier, 2020)
Qing Dai/Indigo Naturalis (QD) has been shown to ameliorate ulcerative colitis (UC) in clinical trials; however, its mechanism remains elusive. This study investigates the effects of QD on murine dextran sulfate sodium salt-induced colitis. Oral administration of QD protected the animals from colitis as manifested by weight loss, diarrhea, and rectal bleeding. QD was distinguishingly more effective than 5-aminosalicylate. Focused microarray analysis of genes expressed in the distal colon suggested that QD influences the inflammatory pathway. Anti-inflammatory activity of QD was confirmed by the suppression of nitric oxide (NO) production in response to interleukin-1β in cultured hepatocytes. Some of the constituents in QD, such as tryptanthrin (TRYP) and indigo, suppressed NO production. TRYP maintained body weight but did not inhibit bleeding. Indigo, on the other hand, partially ameliorated bleeding, but did not maintain body weight. The combination of TRYP and indigo did not show additive ameliorating activity. The methanol extract of QD showed an anti-colitis activity like that of TRYP. In contrast, the methanol-insoluble QD fraction moderately ameliorated diarrhea and bleeding. Combining these two fractions resulted in full anti-colitis activity. Further clarification of the active constituents will help in the discovery of a safe and potent prescription for UC. Keywords: Ulcerative colitis, Dextran sulfate sodium salt, Qing Dai/Indigo Naturalis, Tryptanthrin, NO